Implementation Dynamics of Passport Service Policy for Dual Nationality Child Subjects in Indonesia - Caesar Demas Edwinarta; Rizkya Dwijayanti (Borong Newinera Publisher, 2024)
Abstract This article is a study of the implementation of passport service policies for children with dual citizenship in Indonesia. The implementation of this policy is the implementation of Permenkumham Number 18 of 2022, one of the points of which regulates the application of passport validity periods for children with dual citizenship. Regulations regarding the validity period of passports for children with dual citizenship are a form of policy that is in direct contact with Government Regulation Number 21 of 2022, although in its application to passport services at the Immigration Office, sometimes there is still no continuity between the two regulations. This then results in an analysis of the implementation of the passport service policy for children with dual citizenship which boils down to 3 decisions, namely first, namely providing a passport with a validity period up to the age limit for choosing the nationality of the passport applicant, postponing the passport application until the passport applicant completes the process of filing his/her citizenship selection, or refusing passport application because the passport applicant cannot complete the documents verifying the validity of his or her citizenship status by the previously determined time limit. The analysis used in this research uses Public Policy theory with the concept of Open Government and Public Policy Implementation in government institutions in Indonesia. It is hoped that this research will be able to provide an overview of the implementation of passport services for children with dual citizenship and provide the best solution for implementing this policy in the future.